The polymerase δ-interacting protein family and their emerging roles in diseases - Huang, Peiluo; Wu, Lei; Zhu, Ningxia; Zhao, Hongtao; Du, Juan (Frontiers in Medicine, 2022)
The polymerase δ-interacting protein (POLDIP) family is a new family that can interact with DNA polymerase δ (delta). The members of the POLDIP family include POLDIP1, POLDIP2, and POLDIP3. Screened by the two-hybrid method, POLDIP1, POLDIP2, and POLDIP3 were initially discovered and named for their ability to bind to the p50 subunit of DNA polymerase δ. Recent studies have confirmed that POLDIPs are involved in the regulation of signal transduction pathways in neurodevelopment, neuropsychiatric diseases, cardiovascular diseases, tumors, and other diseases. However, each protein participates in different signaling pathways. In this review, we elucidate upon the family in terms of their genes and protein structures, their biological functions, in addition to the pathways that they are involved in during the development of diverse diseases. Finally, to provide new insights to the scientific community, we used the TCGA database to analyze and summarize the gene expressions of POLDIP family members in various tumors, as well as the correlations between their expressions and the overall survival times of tumor patients. Our data summary will give researchers working on cancer new concepts.